Traumatic characters' re-victimisation through death instinct in selected Malaysian noir narratives - Mohd Noor, Nurul Soleha; Ali Termizi, Arbaayah (Universiti Teknologi PETRONAS, 2023)
Sigmund Freud first coined the concept of ˜death instinct in his controversial work Beyond the Pleasure Principle (1920) by stating that all beings are driven towards death as the result of living. The concept was introduced to explain the reasons for traumatised individuals to undergo a ˜compulsion to repeat their traumatic state. This concept will be applied to the textual analysis of selected characters who had undergone traumatic experience(s) from three Malaysian noir short stories published by Fixi Novo and written by three different authors. These stories were chosen since they took place in an urban community with its storyline regulating sexual abuse that leads to murder. The paper aims to (a) identify the traumatic event(s) experienced by selected characters in the short stories which provoke(s) their primal ˜death instinct and (b) examine how the concept ˜death instinct by Sigmund Freud compelled selected characters to repeat their trauma outwardly to undo their trauma. The study discovered that ˜death instinct is crucial as an intrinsic force to help victims of trauma psychically undo their traumatic experience by repeating the act of violence upon others as a disguised form of self-gratification in response to a traumatic condition of urban society.